Between Two Worlds : My Life As a Child of Deaf Adults. - Sorensen, David (Gallaudet University Press, 2019)
In his memoir, David Sorensen explores his identity as a Coda, or a child of Deaf adults. He describes his experiences with the roles often placed on Codas at a young age, such as interpreter, confidant, and decision-maker. His story reveals a person seeking acceptance and belonging while straddling the Deaf and hearing worlds and shows how he found reconciliation within himself and with both worlds. Sorensen relays the dynamics of his family life; he had a strained relationship with his father, who was an active leader and role model in the Deaf community and the Mormon Church, yet struggled to bond with his own son. Sorensen rebelled as a youth and left home as a teenager, completely detaching from the Deaf community. After struggling to establish himself as an independent adult, he discovered that he wanted to return to the Deaf world and use his ASL fluency and cultural understanding to be a mental health therapist and community advocate. Now he considers himself an ambassador between the Deaf and hearing worlds, as well as between the older and younger generations of Deaf people. Between Two Worlds: My Life as a Child of Deaf Adults shares the unique experiences of a Coda and passes on the rich cultural past shared by the American Deaf community.